Pengaruh Lingkungan Kerja Fisik Terhadap Semangat Kerja Pegawai Pada Kantor Camat Woha Kabupaten Bima - Adithya Dwisaputra; Jaenab Jaenab (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Human resources are important in the organization. The importance of human resources in an organization demands that the organization gets quality and productive employees in the organization, Annisa.N.(2015) In addition, the organization or company must also provide a special section related to employees, this section is called resource management human (MSDM). Human resource management is what makes an organization able to carry out daily activities. Many employees in organizations have different personalities, values, needs, expectations, thoughts and behaviors. The differences that arise from each of these individuals require that each leader or manager be able to integrate, communicate, direct, and align any differences that exist so that they can become a source of strength in achieving organizational goals. Besides that, to support the performance of an employee requires motivation in working either from the work environment or from the level of morale possessed by human resources.